2018
DOI: 10.3892/etm.2018.6141
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of melatonin combined with calcium carbonate on improving osteoporosis in aged rats

Abstract: The effects of melatonin and calcium carbonate on aged rats with osteoporosis (OP) were assessed. Forty female Sprague-Dawley (SD) rats aged 15 months were randomly divided into a model group (group OP), melatonin group (group M), calcium carbonate group (group Ca) and melatonin combined with calcium carbonate group (group M+Ca), while 10 rats aged 3 months were set as the control group (group NC). The changes of bone density and bone mineral level of lumbar vertebra and bilateral femur in rats of each group w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…The indole hormone MLT influences bone metabolism by promoting bone matrix mineralization through the modulation of different signal transduction pathways . Previous studies, mainly carried out in animal models of osteoporosis, examined the safety and efficacy of MLT administered with different strategies and dosages.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The indole hormone MLT influences bone metabolism by promoting bone matrix mineralization through the modulation of different signal transduction pathways . Previous studies, mainly carried out in animal models of osteoporosis, examined the safety and efficacy of MLT administered with different strategies and dosages.…”
Section: Discussionsupporting
confidence: 52%
“…43,61 The indole hormone MLT 26 influences bone metabolism by promoting bone matrix mineralization through the modulation of different signal transduction pathways. 62 Previous studies, mainly carried out in animal models of osteoporosis, examined the safety and efficacy of MLT administered with different strategies and dosages. Ladizesky et al 63 demonstrated an increase in bone alkaline phosphatase in ovariectomized rats receiving 25 µg/mL of MLT in drinking water compared with control rats.…”
Section: Discussionmentioning
confidence: 99%
“…NAC was injected once every 2 weeks for a total of 5 times. The dosage of TFRD and CaCO 3 was selected based on the research reports of Fang et al (21) and Zhu et al (22).…”
Section: Experimental Animalsmentioning
confidence: 99%
“…Our research also demonstrated that MT can enhance bone microstructure and bone metabolism in rodents with oophorectomized osteoporosis. Despite the fact that numerous studies ( 29 32 ) suggest MT can reduce the harm caused by oxidative stress and inflammation to osteoblasts, as well as ward off osteolysis caused by reactive oxygen species and inflammatory factors, we still believe MT can be beneficial for the health of bone structure through its control of bone microenvironment and metabolism. Nevertheless, further research is needed for its clinical application in the prevention and treatment of osteoporosis.…”
Section: Discussionmentioning
confidence: 94%